2013
DOI: 10.1002/chem.201203357
|View full text |Cite
|
Sign up to set email alerts
|

E/Z Oxime Isomerism in PhC(NOH)CN

Abstract: The reaction of nitric oxide with benzyl cyanide in the presence of potassium methoxide at low temperature gave the dipotassium salt of a bis-diazeniumdiolate 2 in excellent yield. Two new stereospecific syntheses of E or Z 2-(hydroxyimino)-2-phenylacetonitrile from 2 have been found. The thermodynamics of the E/Z isomerization has been investigated spectroscopically in solution, in the solid state by differential scanning calorimetry (DSC), and theoretically in the gas phase. Evidence of catalysis by NO of E/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…As imilar shift for 2-trimethylammonio-6-hydroxybenzaldehyde oximes wasreported previously by Radić et al [13n] Twodissociation constants were observed for oximes 16 and 18 in the pH range studied, most likely corresponding to the dissociation of the oxime (=NÀOH) and the hydroxy group (ÀOH) on the pyridinium ring, because the absorption at 360 nm is presumed to originate from p!p*t ransitionsw ithin the pyridinium aromatic system. [32] Because strongi somerisation of the oxime group is expected only in as trong acidic environment, [33] only the spectra recorded in solutions of pH ! 6w ere studied.…”
Section: In Silico and In Vitro Determination Of Pk A Valuesmentioning
confidence: 99%
See 1 more Smart Citation
“…As imilar shift for 2-trimethylammonio-6-hydroxybenzaldehyde oximes wasreported previously by Radić et al [13n] Twodissociation constants were observed for oximes 16 and 18 in the pH range studied, most likely corresponding to the dissociation of the oxime (=NÀOH) and the hydroxy group (ÀOH) on the pyridinium ring, because the absorption at 360 nm is presumed to originate from p!p*t ransitionsw ithin the pyridinium aromatic system. [32] Because strongi somerisation of the oxime group is expected only in as trong acidic environment, [33] only the spectra recorded in solutions of pH ! 6w ere studied.…”
Section: In Silico and In Vitro Determination Of Pk A Valuesmentioning
confidence: 99%
“…R f = 0.45 (cyclohexane/EtOAc, 1:1, v/v); 1 HNMR (300 MHz, CDCl 3 ): d = 1. 33 Reversible inhibition and reactivation measurements:S tock solutions of the oximes were prepared in DMSO (Kemika, Zagreb, Croatia), methanol (Kemika, Zagreb, Croatia) or water.F urther dilutions were prepared in water or 0.1 m sodium phosphate (pH 7.4). HI-6 dichloride monohydrate was ag ift from Dr.K amil Kučaa nd Dr. Daniel Jun (Faculty of Military Health Sciences, University of De-fence, Hradec Kralove, Czech Republic).…”
Section: Methylmentioning
confidence: 99%
“…The a-oximation reactions were performed at room temperature in dimethylformamide( DMF) with NaNO 2 and FeCl 3 in the presence of pyrrolidine as organocatalystt o give the products in satisfactory (45 %) to excellent yields (90 %). [1] Briefly,1 ,6-hexanediol was monoacylated with methacrylic anhydride, and the resulting 6-hydroxyhexylm ethacrylate (17)w as oxidized to the corresponding aldehyde 4 through Parikh-Doeringo xidation. [5] HIA 12 was obtained in good yield by am ultistep synthesis that we recently reported (Scheme 2).…”
Section: Synthesis Of Hiasmentioning
confidence: 99%
“…[12] and references therein). [17] HIAs are expected to possess al ower pK a than the corresponding unsubstitutedo ximes, so that it is of paramount importance to determine their acidity in view of the possible applications in which oximate ions are involved. The interaction between the adjacent aldehyde and oxime groups in HIAs, mainly hydrogen bonding and the conjugation of the oximate anion, is likely to be different in the two configurations, thus resulting in distinct physicochemicalp roperties.…”
Section: Introductionmentioning
confidence: 99%
“…Given the poor nucleophilicity of the diarylamine groups used here, we sought to clarify some of these mechanistic questions with density functional theory. 47 In prior publications, we have found that B3LYP/6-311++G** is an excellent combination of method and model for the ground-state geometries and vibrational modes or electronrich nitrogen species with multiple lone pairs such as these. 48,49 Here, the inclusion of diffuse functions is an important factor.…”
Section: Resultsmentioning
confidence: 99%